Dendrobium candidum extract on the bioactive and fermentation properties of Lactobacillus rhamnosus GG in fermented milk. (June 2021) - Lei, Wenping; Luo, Jie; Wu, Ku; Chen, Qi; Hao, Lulu; Zhou, Xingrong; Wang, Xianyue; Liu, Chengguo; Zhou, Hui
Abstract: Dendrobium candidum has a long medicinal history and good nutritional value. It has been used in the health food industry. However, the effect of D. candidum on the biological activity and the fermentation of probiotics need further study. This study evaluated the effect of D. candidum extract (DCE) on the chemical, viable bacteria count, and acid production capacity of milk fermented using probiotics. The tolerance of Lactobacillus rhamnosus GG (LGG) to simulated gastrointestinal fluids, the ability of the strain to scavenge free radicals, adhesion capacity, and antibacterial activity were measured. The differences in volatile flavor substances and sensory properties of fermented milk with and without DCE added were measured. The results showed that DCE supplementation increased the use of proteins and carbohydrates by LGG, and rate of carbohydrate using LGG increased by 25%. The growth and acid production ability of the strain were increased. The number of viable bacteria in the fermented milk with DCE supplementation was >8.5 log CFU/mL, and the survival rates of LGG in simulated gastric and intestinal juices were improved. O2 − and hydroxyl radicals in the fermented milk samples with DCE added were significantly decreased. In addition, DCE did not significantly affect the flavor quality of fermented milk. DCE supplements are a promising type of transfer protection agent. Graphical abstract: Image 1